Comparison of Seepage Trough Zoned Earth dam Using Improved Light-Textured Soils (Journal of Engineering, 2022)
Seepage through earth dams is one of the most popular causes for earth dam collapse due to internal granule movement and seepage transfer. In earthen dams, the core plays a vital function in decreasing seepage through the dam body and lowering the phreatic line. In this research, an alternative soil to the clay soil used in the dam core has been proposed by conducting multiple experiments to test the permeability of silty and sandy soil with different additives materials. Then the selected sandy soil model was used to represent the dam experimentally, employing a permeability device to measure the amount of water that seeps through the dam's body and to represent the seepage line. A numerical model was adopted using Geo-Studio software in the branch (SEEP/W)  to simulate the experimental model, examined soils with different percentages of additives, and compared the numerical and experimental results to predict the innovation model of soil. It was found that the sandy type (C) soil model has a permeability very close to that of clay soil when using 10% cement kiln dust (CKD) and 5% cement as additives. Furthermore, soil type (C) was calibrated with the core soil of HIMREEN Earth dam, which is clay soil, as well as with the core soil of HADITHA Earth dam, which is composed of dolomite. The comparison between the results of the hypothetical simulated cases and the real cases were revealed a high agreement between the two cases according to the resulted of identical phreatic (seepage) lines and the calculated amount of seepages water from these cases.